The prevalence of obstetric violence experienced by women during childbirth care and its associated factors in Türkiye: A cross-sectional study - (:unkn) unknown (My University, 2023)
Objective This study determined the prevalence of obstetric violence experienced by women during childbirth and related factors in Türkiye. Design Cross-sectional study Setting This study was conducted in the mother-child health and gynecology outpatient clinics of the training and research hospital in Türkiye. Participants The study was completed with 513 women who gave birth in the last two years between January and May 2022. Methods Data were collected using a questionnaire prepared by the researchers. Bivariate and multivariate logistic regression analyzed the relationship between obstetric violence and socio-demographic and obstetric characteristics. Findings Obstetric violence was reported by 76.4% of the women: 44.4% physical abuse, 44.4% abandonment of care, 26.5% non-consented care, 25.1% non-dignified care, 3.3% non-confidential care, and 0.4% discrimination. Low income (OR=1.98), physician-attended birth (OR=2.91), vaginal birth (OR=6.04), and newborn admission to the neonatal care unit (OR=2.99) were associated with higher reporting of obstetric violence. Primiparous women (OR=0.51), whose pain was controlled by non-pharmacological methods (OR=0.34) and who received companion support (OR=0.24) were less likely to report experiencing obstetric violence (p < 0.05). Key conclusions Approximately three out of four Turkish women report that they have been exposed to obstetric violence during childbirth. In Türkiye, vaginal birth is the type of childbirth with the highest rate of obstetric violence reporting. Women who are low-income and multiparous, who are deprived of midwife, companion, and pain control support during childbirth, are more likely to experience obstetric violence. Implications for practice Supporting low-income women, protecting women from traumatic acts and unnecessary interventions in a vaginal birth, increasing births under the attendance of midwives, and providing pain control with non-pharmacological methods, and companion support during labor may be protective factors against obstetric violence.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Kadın Hastalıkları ve Doğum; Hemşirelik; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Obstetrics and Gynecology; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; KADIN HASTALIKLARI & DOĞUM; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; OBSTETRICS & GYNECOLOGY; Doğum ve Jinekoloji; Annelik ve Ebelik; Maternity and Midwifery; Childbirth; Obstetric violence; Türkiye; Women's health